Mathematical Techniques for Circulatory Systems - Raoul van Loon (Reference Module in Biomedical Sciences, 2018)
This article provides an overview on how human circulation is computationally modeled. The discussion presented explains all the latest development in the field and emphasizes the areas that need research focus. The article consists of fundamentals of the circulation, mathematical models, dealing with arterial and venous systems, organs, microcirculation, and parameters involved. The discussion also provides details on why certain parameters are difficult to obtain. The article also accounts in detail the computational models used to solve flow circulation. Although interesting to understand the modeling of circulation, the models should be useful and insightful. This article discusses the usefulness of circulation models and their limitations.